Conspiracy of silence [large type] - Kendig, Ronie (The Tox files, 2017)
"When an archaeological dig unleashes a centuries-old virus, paramilitary operative Cole 'Tox' Russell is forced back into action. As his team races to stop a pandemic, a secret society counters their every move"--